Buddhist Homiletics on Gambling (*Saddharmaparikathā, Ch. 12) - Szántó, Péter-Dániel (Indo-Iranian journal, 2022)
The paper focuses on the 12th chapter of the *Saddharmaparikathā, a Buddhist homileticians’ guidebook containing sample sermons, dealing with the topic of gambling (dyūta). I edit, translate, and discuss the chapter with an introduction that includes a short overview of gambling in Sanskrit literature at large. The anonymous author is dismissive of gambling in all its forms, whether it is practised for material gain, for mere pleasure, and even if studied as an art. In spite of its exiguity, his discussion of the topic is, as far as we are aware, the most comprehensive in classical Buddhist literature.